2010
DOI: 10.4103/0253-7613.66845
|View full text |Cite
|
Sign up to set email alerts
|

Zidovudine-induced reversible pure red cell aplasia

Abstract: Hematological abnormalities are frequent among human immunodeficiency virus (HIV)-infected patients and may be directly attributable to the virus or may be caused by opportunistic infections, neoplasms or drugs that cause bone marrow suppression or hemolysis. Pure red cell aplasia (PRCA) is an uncommon hematological disorder that causes anemia. We report a 37-year-old male with HIV infection who developed PRCA 6 weeks after commencing Zidovudine and recovered following cessation of the drug. This is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…In spite of having so much of beneficial record of AZT [ 22 ], the previous (pharmacokinetics) PK studies showed that, AZT is responsible for the bone marrow toxicity [ 23 ] which leads to bone marrow suppression [ 24 ] and finally results to various alteration related to hematopoiesis [ 25 – 27 ]. Further AZT has been proven as a genotoxic compound [ 28 , 29 ] which cause the induction of micronuclei in the mouse bone marrow cells [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of having so much of beneficial record of AZT [ 22 ], the previous (pharmacokinetics) PK studies showed that, AZT is responsible for the bone marrow toxicity [ 23 ] which leads to bone marrow suppression [ 24 ] and finally results to various alteration related to hematopoiesis [ 25 – 27 ]. Further AZT has been proven as a genotoxic compound [ 28 , 29 ] which cause the induction of micronuclei in the mouse bone marrow cells [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…ZDV is associated with hematologic toxicity including neutropenia and anemia, particularly in patients with advanced HIV-1 disease. In addition, pure red cell aplasia occurs with ZDV after 6 weeks to 4 years of therapy 2426 .…”
Section: Discussionmentioning
confidence: 99%
“…59 AZT is associated with macrocytosis, 62 but rarely associated with severe anaemia as a result of a pure red cell aplasia. 64 If there is adequate time remaining in the pregnancy, patients who are treatment-naïve, do not qualify for full ART, and have an Hb <10g/dl, should receive a full course of haematinics and their response observed. Their response should be re-assessed after 2 weeks and, if there is a response, AZT be commenced.…”
Section: Transfusion Medicine Best Practicementioning
confidence: 99%